PERCEPTION OF FKG UPDM(B) PRE-CLINIC STUDENTS ABOUT THE EXPERIENCE OF ORTHODONTIC TREATMENT DURING COVID-19 - Uno, Salsabila Putri; Pakpahan, Evie Lamtiur (Universitas prof. Dr. Moestopo (Beragama), 2024)
Understanding perceptions regarding patients experiences of orthodontic treatment during the COVID-19 pandemic is important. This can describe how patients view orthodontic treatment during the COVID-19 pandemic, and in understanding the problems faced during the COVID-19 pandemic. Purpose: To explain the perceptions of orthodontic patients about the experience of orthodontic treatment during COVID-19. Methods: Descriptive study with a cross-sectional design. The number of research subjects was 47 students of pre-clinical FKG UPDM(B) who used orthodontic devices by distributing online questionnaires. Results: Based on questionnaires in this research majority of patients felt no pain (44,7%) also no discomfort (44,7%) using the orthodontic appliance. During the COVID-19 pandemic, orthodontic treatment was delayed (40,4%), and they felt needed an additional six months (31,9%). Patients communicated directly with orthodontist and performed routine checks monthly (55,3%). Patients are happy with the protocol at the clinic (51,1%). Patients prefer orthodontist to use PPE with N-95 masks when performing orthodontic treatment (80,9%). Patients feel confident about continuing orthodontic treatment during the COVID-19 pandemic (76,6%). Conclusion: Majority of orthodontic patients are optimistic about continuing orthodontic treatment during COVID-19; as many as 36 people are confident, and 11 are pretty sure.